Efinaconazole in the treatment of onychomycosis - Lipner, Shari R (Infect Drug Resist, 2015)
Efinaconazole 10% topical solution is a new triazole recently approved for the treatment of onychomycosis. It inhibits fungal lanosterol 14α-demethylase in the ergosterol biosynthesis pathway, has potent antifungal activity against dermatophytes, as well as activity against Candida spp. and non-dermatophyte molds, and showed promising results in clinical trials. This review summarizes the mechanism of action, in vitro and in vivo data, clinical trials, safety, and quality-of-life data of efinaconazole as it applies to the treatment of onychomycosis.